Special modified calcium carbonate for polypropylene composite material as well as preparation method and application of special modified calcium carbonate
By coating the crosslinked dextran on the surface of calcium carbonate, its compatibility with polypropylene is enhanced, and the problems of low-temperature brittleness and poor compatibility of inorganic fillers of polypropylene materials are solved, which significantly improves its mechanical and thermal stability properties. , expanding the scope of application.
Patent Information
- Application Number
- CN202411298497.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Polypropylene materials do not perform well in low temperature brittleness, mechanical strength and hardness, and the inorganic fillers have poor compatibility with polymer matrix, which affects their overall performance.
By covering the crosslinked dextran on the surface of calcium carbonate, a modified layer is formed to enhance the compatibility of calcium carbonate with polypropylene, and its mechanical properties and thermal stability are improved.
It significantly improves the impact strength, tensile strength and thermodynamic properties of polypropylene composite materials, broadens its application range, and meets high-performance requirements.
Smart Images

Figure SMS_1 
Figure HDA0005046859540000011 
Figure HDA0005046859540000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new organic polymer materials and products, and particularly relates to a modified calcium carbonate special for polypropylene composite materials and a preparation method and application thereof. Background Art
[0002] Polypropylene (PP) is a thermoplastic made by polymerizing propylene monomers. It is known for its abundant raw materials and simple synthesis process. Compared with other general-purpose plastics, polypropylene has the characteristics of low density, high cost-effectiveness, and excellent processing performance. Its mechanical properties, including yield strength, tensile strength, surface hardness and elastic modulus, are excellent. In addition, polypropylene also exhibits excellent resistance to stress cracking, chemical corrosion and wear resistance. Its softening point is higher than that of high-density polyethylene (HDPE) and acrylonitrile-butadiene-styrene (ABS) copolymers, and it has good electrical insulation properties and a low dielectric constant, making it widely used in automobiles, home appliances, engineering and other fields.
[0003] However, pure polypropylene (PP) also has some limitations, such as brittleness at low temperatures, relatively low mechanical strength and hardness, large molding shrinkage, easy aging and poor high temperature resistance, which limit its promotion in a wider range of applications.
[0004] The crystallinity and phase diversity of polypropylene have a significant impact on its performance. PP is a polycrystalline semi-crystalline polymer with different crystal forms such as α, β, γ, δ and pseudo-hexagonal. Among them, the α crystal form is a monoclinic system and is the most thermodynamically stable crystal form. It has a large spherulite size, clear grain boundaries and a high degree of perfection, which gives the polymer good rigidity but poor toughness. The β crystal form is a hexagonal system with a small spherulite size and unclear grain boundaries. Its crystalline polymer exhibits good toughness and resistance to heat deformation, but has low thermodynamic stability and usually requires special methods to prepare. In contrast, the γ, δ and pseudo-hexagonal crystal forms are low in content and unstable. They are only formed under specific conditions and have limited practical value.
[0005] The crystallization behavior and crystal characteristics of polypropylene are closely related to its performance. Different crystal phases and crystallinity have an important influence on the physical, chemical and thermal properties of the material. Therefore, by controlling the crystallization conditions of polypropylene and adding specific nucleating agents or modifiers, its crystallinity and crystal phase can be adjusted, thereby optimizing its performance to meet specific application requirements.
[0006] In order to expand the application range of polypropylene (PP) materials and improve their comprehensive performance, modification measures must be taken. These modification measures include chemical modification, such as copolymerization, grafting, and cross-linking of PP; and physical modification, including fiber reinforcement, inorganic rigid particle filling, organic elastic particle filling, and inorganic-organic mixed particle filling. Domestic and foreign scholars have conducted extensive research on this. However, the existing modification methods often lead to a decrease in other properties while improving the performance of one aspect of PP materials. For example, although the addition of elastic particles can improve the impact resistance of PP and reduce low-temperature brittleness, it will significantly reduce the rigidity and hardness of the material. Glass fiber reinforced PP can significantly improve the strength and rigidity of the material, but may damage its impact resistance. Filling PP with inorganic rigid particles helps to improve the stiffness, hardness and impact resistance of the material, but may reduce the tensile strength of the material.
[0007] Given the high comprehensive performance requirements for PP materials in the automotive and engineering fields, new modification ideas and methods must be explored. This may involve the development of new modifiers, innovative processing technologies or multiphase composite strategies to achieve balanced and optimized performance of PP materials. By comprehensively considering the advantages and limitations of different modification methods, a modification scheme can be designed that can maintain the original advantages of PP and significantly improve its performance.
[0008] In the filling and modification of plastics, the fillers used are usually natural or synthetic inorganic materials. These inorganic fillers, including salts, oxides and metal powders, are water-insoluble substances with strong polarity. When these inorganic fillers are dispersed in the organic polymer resin matrix with low polarity, due to the difference in polarity, the compatibility between the filler and the resin may be poor, which in turn has an adverse effect on the processing and use performance of the modified plastic.
[0009] Therefore, it is crucial to properly treat the surface of the inorganic filler to adjust its surface polarity through chemical reactions or physical methods to improve its compatibility with the filled polymer resin. The mechanism of action of filler surface treatment can be divided into two categories: 1. Surface physical action: involving surface coating (or coating) and surface adsorption. In this case, the bonding between the filler and the treatment agent is mainly achieved through intermolecular forces. 2. Surface chemical action: including chemical reactions such as surface substitution, hydrolysis, polymerization and grafting. This type of treatment method creates a strong bond between the filler surface and the treatment agent through the formation of chemical bonds. Comprehensive consideration of the surface treatment methods of inorganic fillers can effectively improve their compatibility with organic polymer resins, thereby optimizing the comprehensive performance of filled modified plastics.
[0010] In the field of filled and modified plastics, the surface characteristics of fillers have a significant impact on material properties. Generally speaking, fillers with larger specific surface area, higher surface functional group density and stronger reactivity have higher reaction rates with surface treatment agents, and have less steric hindrance, and tend to bind to the filler surface through chemical bonding. On the contrary, if the steric hindrance is large, physical effects (such as van der Waals forces) may become dominant. In practical applications, the surface treatment of most fillers involves the coexistence of physical and chemical effects.
[0011] For a specific filler, choosing different surface treatment agents will lead to different surface modification mechanisms. When using surfactants, long-chain organic acid salts or high-boiling-point chain hydrocarbons as surface treatment agents, filler surface modification is mainly achieved through physical effects, such as surface coating or adsorption. When using coupling agents, organic silane compounds or epoxy compounds as surface treatment agents, surface modification is mainly achieved through chemical effects, such as covalent bonding between functional groups.
[0012] The goal of filler surface modification is to optimize the compatibility between filler and resin matrix and improve the mechanical properties, thermal stability and processing performance of composite materials. Therefore, the selection of appropriate surface treatment agents and methods is crucial to achieve the expected material properties.
[0013] Among many inorganic fillers, calcium carbonate is widely used due to its significant advantages. Calcium carbonate has the characteristics of abundant resources, low cost, easy raw material availability, easy storage and transportation, easy color adjustment and little wear on processing equipment. Calcium carbonate has various forms, including calcium carbonate whiskers, nano calcium carbonate, light calcium carbonate, heavy calcium carbonate, colloidal calcium carbonate and activated calcium carbonate, etc. These characteristics make calcium carbonate a commonly used additive in plastic products, especially hard plastic products.
[0014] However, as a polar filler, calcium carbonate has poor compatibility with non-polar polypropylene polymer. Adding large amounts of calcium carbonate to the polypropylene matrix may cause microcracks or pores inside the material, which will affect the mechanical properties and durability of the final product. Therefore, it is particularly important to properly modify the surface of calcium carbonate or polypropylene to enhance the compatibility between the inorganic filler and the polymer matrix.
[0015] Surface modification can be achieved by chemical or physical methods, with the goal of improving the interfacial interaction between filler and resin, reducing interfacial tension, improving dispersibility and overall composite performance. This may involve the use of coupling agents, surfactants or other specialized surface modifiers to promote compatibility between calcium carbonate and polypropylene, thereby improving the mechanical properties and processing properties of the material.
[0016] Early research focused on increasing the hydroxyl content of filler surfaces through hydroxylation treatment, and further research was conducted based on the amount of hydroxyl content. Studies have found that inorganic fillers with surface hydroxylation can introduce more coupling agents, and different types of coupling agents have different effects on filler properties. As research deepens, new coupling agents with unique structures have been developed.
[0017] Subsequently, researchers began to explore the grafting of small organic molecules onto coupling agents, and further developed to the grafting of macromolecular polymers. However, these methods usually involve multi-step reaction processes and may face challenges in feasibility and cost control in industrial applications. Therefore, researchers seek simpler modification methods, such as fixing functional groups on the surface of inorganic fillers through cross-linking technology.
[0018] At present, commonly used grafting monomers include acrylic acid, maleic acid and its anhydride, acrylic acid epoxy ester, maleic anhydride, etc. The diversity of grafting methods includes solution method, melt method, solid phase grafting technology, in-situ reaction grafting technology and mechanochemical melt grafting technology.
[0019] In order to directly improve the compatibility of inorganic fillers with the matrix, an efficient method is to graft functional groups compatible with the matrix on the surface of the filler. On this basis, the researchers further explored the effect of this method on improving the mechanical properties of the material. By continuously modifying the surface of the inorganic filler to meet specific application requirements, the most important goal is to enhance the compatibility of the inorganic filler with the polymer matrix, thereby optimizing the comprehensive performance of the composite material.
[0020] At present, the modification technology for inorganic filler calcium carbonate is mainly divided into two types: dry method and wet method. The modified calcium carbonate usually shows lipophilic properties to better adapt to the non-polar nature of polypropylene. Dry modification is favored for its advantages such as simple operation, no need to remove solvents and easy processing; while wet modification is known for its better dispersibility and modification effect. Summary of the invention
[0021] In order to overcome the shortcomings and deficiencies in the prior art, the primary purpose of the present invention is to provide a method for preparing modified calcium carbonate specifically for polypropylene composite materials.
[0022] Another object of the present invention is to provide a modified calcium carbonate specially used for polypropylene composite materials prepared by the above preparation method.
[0023] Another object of the present invention is to provide an application of modified calcium carbonate specifically for the above-mentioned polypropylene composite material.
[0024] The purpose of the present invention is achieved through the following technical solutions:
[0025] A method for preparing modified calcium carbonate specifically for polypropylene composite materials comprises the following steps:
[0026] Calcium carbonate is added to a dextran solution, the temperature is raised to 45-55° C., glutaraldehyde is added, and magnesium salt is added as a catalyst, the pH value is adjusted to 5-7 with 1% mass percent sulfuric acid, the reaction is carried out at 45-55° C. for 5-7 hours, and after the reaction is completed, the filter residue is filtered and dried at a temperature of ≤100° C. to a water content of no more than 0.2wt% to obtain coated calcium carbonate, i.e., modified calcium carbonate specially used for polypropylene composite materials.
[0027] The coated calcium carbonate is composed of calcium carbonate and a modified layer on its surface, wherein the mass ratio of calcium carbonate to the modified layer is 100:(0.25-8).
[0028] The dextran solution is obtained by adding dextran into water and stirring and dissolving it for 10 to 60 minutes; the molecular weight of the dextran is 1500-500000. The molecular weight of the dextran will not significantly affect the performance of the coated calcium carbonate under a certain quality.
[0029] The mass ratio of dextran to glutaraldehyde in the dextran solution is 1:1 to 3. Different molar ratios of dextran to glutaraldehyde result in different cross-linking degrees, which in turn affect the hydrophilicity and effect.
[0030] The magnesium salt is MgCl2 or MgSO4, preferably MgCl2. MgCl2 is used to form ion reaction with hydroxyl groups on dextran during the preparation process to improve the flexibility of the modified layer, but other methods that can provide magnesium ions, such as magnesium sulfate, can also be used as an alternative.
[0031] During the preparation process, sulfuric acid is not the only choice for adjusting the pH value. Other alternative acids include carbonic acid, hydrochloric acid, phosphoric acid, citric acid, organic acid, etc., although sulfuric acid is superior in effect.
[0032] If the dry method is adopted, the temperature is directly raised to 90-100° C. after the reaction is completed to dry out the water to obtain coated calcium carbonate.
[0033] A modified calcium carbonate prepared by the above preparation method.
[0034] The modified calcium carbonate is used in the preparation of a polypropylene composite material, wherein the polypropylene composite material consists of the following components: 5-50 parts by weight of modified calcium carbonate and 100 parts by weight of isotactic polypropylene.
[0035] The principle of the present invention is:
[0036] The surface of calcium carbonate is rich in hydroxyl functional groups, and its inherent hydrophilicity limits its application in non-polar polymer matrices. The present invention solves this problem by coating cross-linked dextran on the surface of calcium carbonate. Dextran is a hydrophilic chemical substance with a polyhydroxy structure and is easily soluble in water. Glutaraldehyde is used as a cross-linking agent, and the aldehyde groups at both ends of its molecule can react with hydroxyl groups. Through the mediation of glutaraldehyde, the present invention promotes the formation of chemical bonds between the hydroxyl groups on the surface of calcium carbonate and the hydroxyl groups of dextran. This chemical cross-linking not only enhances the adhesion of dextran on the surface of calcium carbonate, but also significantly improves the compatibility of calcium carbonate with polypropylene matrix. By adjusting the molar ratio of calcium carbonate to dextran, coating effects of varying degrees can be achieved. At the same time, by adjusting the molar ratio of dextran to glutaraldehyde, the process of the cross-linking reaction can be accurately controlled, thereby adjusting the hydrophilicity and lipophilicity of the product. Specifically, the number of hydroxyl groups determines the surface properties of the calcium carbonate / dextran complex, i.e., its hydrophilicity or lipophilicity. By precisely controlling the reaction conditions, the present invention can prepare a calcium carbonate / dextran composite material with specific surface properties to meet specific application requirements, thereby optimizing the compatibility of the inorganic filler with the polypropylene matrix and improving the comprehensive performance of the composite material.
[0037] In the prior art, the commonly used organic chains are relatively short and have a relatively small molecular weight, making it difficult to form effective entanglements with the polypropylene matrix, thereby limiting the improvement of compatibility. In contrast, the present invention uses a high molecular weight polysaccharide polymer as a modifier, giving calcium carbonate modification a unique advantage. Due to the high molecular weight characteristics of polysaccharide, its longer molecular chains can form more entanglements with the polypropylene matrix, thereby significantly improving the compatibility between the two and reducing the phase separation phenomenon. This modification method not only improves the mechanical properties of polypropylene, but also improves its thermodynamic properties, including but not limited to parameters such as crystallization temperature and melting temperature. The present invention not only improves the compatibility of calcium carbonate and polypropylene through an innovative modification method, but also expands the application range of inorganic fillers, providing new ideas and methods for optimizing the performance of polypropylene-based composite materials.
[0038] Compared with the prior art, the present invention has the following advantages and effects:
[0039] Existing technologies mostly focus on improving the contact angle of calcium carbonate to achieve its transformation from hydrophilicity to lipophilicity; however, the modified calcium carbonate prepared by the present invention can achieve free regulation of the surface properties of calcium carbonate from hydrophilicity to lipophilicity through a specific coating technology; more importantly, the modified calcium carbonate can significantly improve its compatibility with the polypropylene matrix regardless of whether it is in a hydrophilic or lipophilic state; this improved compatibility has a positive effect on multiple properties of polypropylene materials, including enhancing its impact strength and tensile strength, and adjusting its melting temperature and crystallization temperature; the improvement of these properties further broadens the application range of polypropylene composite materials and meets the needs of high-performance applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a schematic diagram of the coating cross-linked network structure formed by cross-linking of glutaraldehyde itself with calcium carbonate and a schematic diagram of the coating cross-linked structure formed by cross-linking of glutaraldehyde with calcium carbonate hydroxyl groups.
[0041] Figure 2 Comparison of infrared spectra of coated calcium carbonate and uncoated calcium carbonate. DETAILED DESCRIPTION
[0042] The present invention is further described below with reference to specific embodiments and drawings, but they should not be construed as limiting the present invention.
[0043] In the first aspect, the present invention relates to a modified calcium carbonate for polypropylene composite materials, wherein the modified calcium carbonate is not limited to the coated form of light or heavy calcium carbonate. The modified calcium carbonate is composed of calcium carbonate and a modified layer on its surface, and the mass ratio of calcium carbonate to the modified layer is 100:(0.25-8).
[0044] The raw materials for preparing the modified layer include dextran with different molecular weights (1500, 40000, 200000, 500000), glutaraldehyde (50% concentration), solid magnesium chloride, and concentrated sulfuric acid or a sulfuric acid solution with a mass percentage concentration of 1%.
[0045] The present invention develops a special modified calcium carbonate according to the structure and performance characteristics of polypropylene. When the modified calcium carbonate is used to prepare a polypropylene composite material, the special modified calcium carbonate is directly mixed into a polypropylene matrix (including block copolymer polypropylene and maleic anhydride grafted polypropylene) in a certain proportion.
[0046] In polypropylene composites, block copolymer polypropylene helps to enhance the mechanical properties of polypropylene; maleic anhydride grafted polypropylene further improves the compatibility of polypropylene with calcium carbonate, thereby optimizing the comprehensive performance of modified calcium carbonate. This modification method can effectively overcome the performance limitations of calcium carbonate and significantly improve the overall performance of polypropylene composites.
[0047] The modified calcium carbonate formula involved in the present invention is the result of in-depth research and multiple experimental explorations to solve the problems faced in the preparation process of polypropylene composite materials. The development of the modified calcium carbonate fully considers the structural characteristics and performance requirements of polypropylene and is specially designed for the application of polypropylene composite materials.
[0048] Therefore, the application of the modified calcium carbonate of the present invention in polypropylene composite materials is highly specific and optimized, while it may not have the same applicability and effect on polymer plastics of other components. This specialized modified calcium carbonate can more effectively solve the specific requirements of polypropylene composite materials in processing and performance, thereby improving the quality and performance of the final product.
[0049] In the present invention, the formula design of the modified calcium carbonate used is carefully studied and verified by experiments. The mass ratio of calcium carbonate to the modified layer has a significant effect on the performance of the modified calcium carbonate (activated) after adding polypropylene. If the mass of the modified layer is too high, it will cause an overly thick coating layer to form on the surface of the calcium carbonate, which will not only reduce the mechanical stability of the coating layer, but also may cause the coating layer to soften and fall off, thereby weakening the effective combination of the modified calcium carbonate and polypropylene. On the contrary, if the mass of the modified layer is insufficient, it is impossible to achieve complete coating of calcium carbonate. After adding polypropylene, calcium carbonate is easy to agglomerate and has poor compatibility with the polypropylene matrix, which limits its addition amount in the composite material.
[0050] After systematic testing and optimization, the inventors found that when the mass ratio of calcium carbonate to the modified layer is controlled within the range of 100:(0.25-8), the best coating effect of calcium carbonate can be obtained. The modified calcium carbonate prepared under this ratio can show excellent comprehensive performance when used in polypropylene composite materials.
[0051] In a second aspect, the present invention provides a method for preparing the modified calcium carbonate specifically for the above-mentioned polypropylene composite material, the method comprising the following steps:
[0052] Wet modification: Dissolve dextran of different molecular weight specifications in water and stir thoroughly to form dextran solutions of different concentrations (mass percentage concentration 0.25% to 8%). Subsequently, calcium carbonate is added to the dextran solution, and glutaraldehyde is added at a temperature of 45-55°C (the amount added is adjusted according to the concentration of dextran, and the mass ratio of dextran to glutaraldehyde is 1:1 to 1:3). At the same time, according to the total amount of the solution, add an appropriate amount of MgCl2 as a catalyst and 1% sulfuric acid to adjust the pH value to 5-7, and react at 45-55°C for 5-7 hours.
[0053] After the reaction is completed, most of the water is removed by filtration, and the calcium carbonate is dried to a water content of less than or equal to 0.2 wt %. During the drying process, it is necessary to control the temperature not to exceed 100° C. to avoid damage to the modified layer due to thermal decomposition.
[0054] The preparation method achieves efficient control of the surface modification of calcium carbonate by precisely controlling the type and amount of the modifier, as well as the reaction conditions, and provides a special modified calcium carbonate with superior performance for the preparation of polypropylene composite materials.
[0055] In a third aspect, the present invention provides a method for preparing modified calcium carbonate specifically for polypropylene composite materials, which belongs to the category of dry modification, and the specific steps are as follows:
[0056] Dextran (different molecular weight specifications are provided, including 1500, 40000, 200000, 500000, etc.) is dissolved in water, and after sufficient stirring and dissolution (10 to 60 minutes), a series of dextran solutions with different concentrations (mass percentage concentration 0.25% to 8%) are formed.
[0057] Add calcium carbonate to the dextran solution and continue stirring until evenly dispersed.
[0058] The mixed solution is heated to 45-55° C., and glutaraldehyde is added. The amount of glutaraldehyde added varies depending on the concentration of the dextran solution, and the mass ratio of dextran to glutaraldehyde is controlled within the range of 1:1 to 1:3.
[0059] According to the total amount of the solution, add an appropriate amount of MgCl2 (1% to 5% solution concentration) as a catalyst to promote the reaction.
[0060] The reaction is maintained at 45-55°C for 5-7 hours, and then the temperature is directly increased to 90-100°C to dry out the moisture.
[0061] In the present invention, the use of magnesium chloride has a regulating effect and can form a complex with the hydroxyl group of dextran, thereby improving the flexibility of the modified layer. As the content of magnesium chloride increases, the softness of the modified layer increases, while also preventing excessive cross-linking and enhancing the biocompatibility of calcium carbonate.
[0062] In addition, sulfuric acid with a mass percentage concentration of 1% is mainly used to adjust the pH value in the present invention. In addition to sulfuric acid, other acid substances such as carbonic acid, hydrochloric acid, phosphoric acid, citric acid, organic acid, etc. can also be used to adjust the pH, but in this experiment, sulfuric acid is used as a strong acid for adjustment, which has a better effect.
[0063] In the dry preparation process, the step of directly heating and drying without filtering is intended to promote the cross-linking reaction of glutaraldehyde. Since glutaraldehyde is alkaline in solution, if the pH value is not adjusted to acidic, glutaraldehyde will remain stable and cannot be cross-linked. Therefore, by adjusting the pH or removing the moisture generated during the reaction, the reaction can be pushed forward to achieve effective cross-linking.
[0064] like Figure 1 As shown, the final synthesized products are glutaraldehyde itself hydroxyl cross-linking and calcium carbonate to form a coated cross-linked network structure, glutaraldehyde and calcium carbonate hydroxyl cross-linking to form a coated cross-linked structure, and the infrared spectrum of the sample is shown in Figure 2 As shown in the infrared spectrum, the blue line is the original infrared spectrum of calcium carbonate, the red line is the original infrared spectrum of dextran, and the black line is the spectrum of the modified calcium carbonate that has been successfully prepared after the reaction, which shows that the synthesis of modified calcium carbonate is successful.
[0065] Finally, the present invention also covers the application of the modified calcium carbonate for polypropylene composite materials in the preparation process of polypropylene-based composite materials. The modified calcium carbonate involved in the present invention, with its excellent stability and fluidity, can meet the strict performance requirements of high-performance polypropylene composite materials for calcium carbonate and its additives.
[0066] The modified calcium carbonate of the present invention is applied in the preparation of polypropylene composite materials, which can significantly increase the addition ratio of calcium carbonate while effectively solving the problems of insufficient compatibility of calcium carbonate with polypropylene, limited addition amount, insufficient material strength, poor dimensional stability and poor thermal stability in the prior art. In particular, in the preparation process of polypropylene, by using the modified calcium carbonate of the present invention, the impact resistance and tensile strength of polypropylene can be significantly improved, thereby preparing a polypropylene composite material with better comprehensive mechanical properties.
[0067] Therefore, the modified calcium carbonate of the present invention not only optimizes the performance of the polypropylene material, but also broadens its potential use in multiple application fields, providing new possibilities for the innovation and development of polypropylene-based composite materials.
[0068] In the present invention, the modified calcium carbonate is used in the polypropylene composite material, and its mass ratio to polypropylene is preferably 10-50%. The modified calcium carbonate comprises calcium carbonate with a specific double-layer coating structure, combined with a specific content of maleic anhydride grafted polypropylene and block copolymerized polypropylene. Compared with calcium carbonate or modified calcium carbonate in the prior art, the modified calcium carbonate of the present invention can significantly increase the addition amount while avoiding the reduction of polypropylene performance, effectively improving the comprehensive performance of polypropylene, and reducing production costs.
[0069] Preferably, the glucan of the present invention changes the number of hydroxyl groups by adjusting the degree of cross-linking to achieve the transformation of the modified layer from hydrophilic to lipophilic. At the same time, the flexibility of the modified layer is adjusted by controlling the content of magnesium chloride.
[0070] The preparation method of calcium carbonate specially used for polypropylene composite materials provided by the present invention has simple process steps, and can efficiently prepare products with stable physical properties and excellent quality by accurately controlling the order of adding materials and process conditions, which is conducive to industrial production and application promotion. The preparation method is specially designed for the structure and composition of modified calcium carbonate specially used for polypropylene composite materials, and provides a special modified calcium carbonate product for the preparation of polypropylene composite materials.
[0071] Unless otherwise specified, the raw materials used in the examples of the present invention are conventional raw materials available on the market, and the equipment and methods used are standard equipment and conventional methods in the technical field.
[0072] In the following examples, the calcium carbonate used has a whiteness of 96-99.5%, a CaCO3 content of not less than 99.5%, and a particle size of 2000 mesh.
[0073] The other raw material specifications used in the examples are as follows:
[0074] The polypropylene is a mixture of PP 1005 produced by Taiwan Plastics Corporation and PT-100 produced by Lee Chang Jung Chemical Corporation in a ratio of 9:1.
[0075] Dextran was provided by Aladdin Biochemical Technology Co., Ltd. with a purity of 99%.
[0076] Magnesium chloride was provided by Shanghai McLean Biochemical Technology Co., Ltd. with a purity of 99%.
[0077] Concentrated sulfuric acid was provided by Guangzhou Anjiehui Trading Co., Ltd. and the purity was industrial grade, 92.5% and 98% respectively.
[0078] Embodiment 1:
[0079] A method for preparing modified calcium carbonate specifically for polypropylene composite materials comprises the following steps:
[0080] Dextran was dissolved in water and stirred thoroughly for 1 hour to form a dextran solution.
[0081] Calcium carbonate was added to the dextran solution and stirred to obtain a mixed solution.
[0082] The mixed solution was heated to 50°C, and then glutaraldehyde was added.
[0083] According to the total amount of the solution, an appropriate amount of MgCl2 was added as a catalyst, and 5 mL of 1% sulfuric acid was added to adjust the pH value to 5-7.
[0084] The preparation process was completed by reacting at 50°C for 6 hours.
[0085] After the reaction is completed, most of the water is removed by filtering, and then the mixture is dried at 80° C. until the water content does not exceed 0.2 wt %, thereby obtaining coated calcium carbonate, which is modified calcium carbonate specially used for polypropylene composite materials.
[0086] In this embodiment, the selection and dosage of each raw material are listed in Table 1 in detail.
[0087] Examples 2 to 6 and Comparative Example 7: The preparation methods of modified calcium carbonate in these examples are the same as those in Example 1, except that the amounts of raw materials used to prepare the coated calcium carbonate are different. The specific amounts of raw materials used to prepare the coated calcium carbonate are also listed in Table 1.
[0088] Table 1 Preparation materials of coated calcium carbonate (parts by weight)
[0089]
[0090] After the preparation process is completed, 10 parts by weight of the modified calcium carbonate sample is mixed with a total of 100 parts by weight of polypropylene. The mixing process is carried out in a double-roll mill set at a temperature of 185°C to ensure that the two materials are fully melted and evenly mixed. Subsequently, the mixed material is processed by compression molding in a flat vulcanizer to form the desired polypropylene composite product. This process ensures good compatibility and dispersibility between the modified calcium carbonate and the polypropylene matrix, thereby obtaining a polypropylene composite material with expected performance; according to the different modified calcium carbonate samples (encapsulated calcium carbonate 1-7 and unencapsulated calcium carbonate 8, respectively), polypropylene composite materials 1-8 are obtained respectively.
[0091] In effect example 1, the touch of coated calcium carbonate samples 1 to 6 was evaluated. By manually grasping these samples, it was observed that the coated calcium carbonate had a relatively sticky feel. However, when pressure was applied and then released, these samples quickly returned to a loose, fine powder state. In addition, when these calcium carbonate samples were placed in water, they showed a faster sedimentation rate due to their hydrophilic characteristics.
[0092] In effect example 2, the impact strength and tensile strength of the polypropylene composite materials 1-8 obtained in the above examples were tested. The specific test methods are as follows:
[0093] Impact strength: It is carried out in accordance with GB / T 1843-2008 standard "Determination of Izod Impact Strength of Plastics". The test samples are prepared by molding method according to GB / T 1843-2008 standard to form impact test samples with A-type notch. Subsequently, the samples are impact tested at room temperature using an impact testing machine, with 5 samples in each group, and the average value is taken as the test result.
[0094] Tensile strength: Prepare the specimens according to the requirements of GB / T 1040.2-2022, and perform the tensile strength test in accordance with the same standard.
[0095] Crystallization temperature and melting temperature were measured using a differential scanning calorimeter (DSC) produced by Mettler-Toledo.
[0096] These test results will provide important data for evaluating the effects of modified calcium carbonate on the properties of polypropylene composites, ensuring that the resulting materials meet high performance requirements.
[0097] Table 2 Tensile strength, impact strength data, crystallization temperature and melting temperature data of polypropylene composites filled with calcium carbonate
[0098] Group Tensile strength / MPa <![CDATA[Impact strength / kJ / m 2 > Crystallization temperature / ℃ Melting temperature / ℃ Polypropylene composite material1 29.81 4.8047 117.12 157.05 Polypropylene composite material 2 28.94 6.0265 120.44 158.54 Polypropylene composite material 3 28.8 5.8745 121.2 162.48 Polypropylene composite material 4 28.12 6.3307 118.41 162.82 Polypropylene composite material 5 28.36 7.3454 122.73 160.33 Polypropylene composite material 6 29.09 5.5081 121.56 161.15 Polypropylene composite material7 28.69 5.4588 120.47 156.98 Polypropylene composite material8 28.11 4.6128 120.76 159.87
[0099] According to the test results in Table 2, it can be observed that the polypropylene composite materials prepared in Examples 1 to 7 exhibit excellent impact strength and tensile strength. In particular, Example 5 is particularly excellent in terms of impact strength, while Examples 1 to 6 are more outstanding in terms of tensile strength. These enhanced mechanical properties are attributed to the good compatibility between the modified calcium carbonate and the polypropylene matrix, thereby achieving significant performance improvements.
[0100] Further analysis of the data in Table 2 shows that Examples 5 and 6 have higher crystallization temperatures, while Examples 3 and 4 exhibit higher melting temperatures. This phenomenon may be related to the thickness of the calcium carbonate modified layer: when the modified layer is thin, the promotion of polypropylene crystallization by calcium carbonate may not be effectively suppressed, resulting in an increase in crystallization temperature; and when the modified layer is thick, the impact strength and tensile strength may decrease due to poor modification effects, as shown in Example 1. In addition, an increase in the dextran content may lead to an increase in cost.
[0101] The above embodiments are relatively suitable implementation modes of the present invention. The implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing modified calcium carbonate specifically for polypropylene composite materials, characterized in that The steps include: Calcium carbonate is added to a dextran solution, the temperature is raised to 45-55° C., glutaraldehyde is added, and then a magnesium salt is added as a catalyst, and the pH value is adjusted to 5-7 with sulfuric acid with a mass percentage concentration of 1%, and the reaction is carried out at 45-55° C. for 5-7 hours. After the reaction is completed, the filter is filtered, and the filter residue is dried at a temperature of ≤100° C. to a water content of no more than 0.2wt%, to obtain coated calcium carbonate, i.e., modified calcium carbonate specially used for polypropylene composite materials.
2. The method for preparing modified calcium carbonate specifically for polypropylene composite materials according to claim 1, characterized in that: The coated calcium carbonate is composed of calcium carbonate and a modified layer on its surface, wherein the mass ratio of calcium carbonate to the modified layer is 100:(0.25-8).
3. The method for preparing a modified calcium carbonate specifically for a polypropylene composite material according to claim 1, characterized in that: The dextran solution is obtained by adding dextran into water and stirring and dissolving it for 10 to 60 minutes; the molecular weight of the dextran is 1500-500000.
4. The method for preparing modified calcium carbonate specifically for polypropylene composite materials according to claim 1, characterized in that: The mass ratio of dextran to glutaraldehyde in the dextran solution is 1:1-3.
5. The method for preparing modified calcium carbonate specifically for polypropylene composite materials according to claim 1, characterized in that: The magnesium salt is MgCl2 or MgSO4.
6. The method for preparing modified calcium carbonate specifically for polypropylene composite materials according to claim 1, characterized in that: After the reaction is completed, the temperature is directly raised to 90-100° C. to dry out the water to obtain coated calcium carbonate.
7. A modified calcium carbonate prepared by the preparation method according to any one of claims 1 to 6.
8. The use of the modified calcium carbonate according to claim 7 in the preparation of a polypropylene composite material, characterized in that: The polypropylene composite material consists of the following components: 5-50 parts by weight of modified calcium carbonate and 100 parts by weight of isotactic polypropylene.
Citation Information
Patent Citations
Organic matter modified calcium carbonate and production method thereof
CN103253692A
Hydrophilia-wrapped water-absorbent resin microsphere and preparation method thereof
CN103408778A
Nano calcium carbonate powder coat-modified with chitosan phosphate crosslinked polymer and preparation method thereof
CN106752099A
Surface modification method for heavy calcium carbonate and method for preparing high polymer composite material through surface modification method
CN107417968A
Method for preparing composite adsorbent from chlorosilane raffinate and chitosan, product prepared therethrough, and use of product
CN108176366A
Cited By
A medical sharp box and a preparation method thereof
CN122706038A